2004
DOI: 10.1097/00005176-200403000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Acidified Milk Formula Supplemented With Bifidobacterium lactis: Impact on Infant Diarrhea in Residential Care Settings

Abstract: These results provide some evidence that viable Bifidobacterium lactis strain Bb 12, added to an acidified infant formula, has some protective effect against acute diarrhea in healthy children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
111
0
7

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(121 citation statements)
references
References 27 publications
3
111
0
7
Order By: Relevance
“…The latter combination exerted prophylactic activity against infectious rotavirus diarrhea in children (Saavedra et al, 1994;Chouraqui et al, 2004). Furthermore, long-term consumption seems to be well tolerated in infants and a significantly lower frequency of colic or abdominal irritability was reported in two different doses of probiotic intake compared to the placebo group (Saavedra et al, 2004).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The latter combination exerted prophylactic activity against infectious rotavirus diarrhea in children (Saavedra et al, 1994;Chouraqui et al, 2004). Furthermore, long-term consumption seems to be well tolerated in infants and a significantly lower frequency of colic or abdominal irritability was reported in two different doses of probiotic intake compared to the placebo group (Saavedra et al, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…BB-12 has been used in clinical trials either alone (Fukushima et al, 1997;Fukushima et al, 1998;Isolauri et al, 2000;Kirjavainen et al, 2002) or together with other bacteria such as Lactobacillus acidophilus LA-5 (Alm et al, 1993;Laake et al, 1999) or Streptococcus thermophilus (Langhendries et al, 1995;Chouraqui et al, 2004;Saavedra et al, 2004). The latter combination exerted prophylactic activity against infectious rotavirus diarrhea in children (Saavedra et al, 1994;Chouraqui et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…S. thermophilus and L. helveticus. 6 Velaphi et al further reported that infants receiving acidified formula had similar growth patterns to those in infants fed a standard whey formula, irrespective of the method of acidification. However, the addition of B. lactis to acidified formula resulted in greater weight gain, compared to that with standard formula.…”
Section: Acidified Formula With Added Probiotic Agentsmentioning
confidence: 95%
“…4 Despite the numerous benefits of breastfeeding, it is not always an option or possible, as many women are unable to, or choose not to, breastfeed. 5,6 A wide range of infant formula is commercially available, including acidified infant formula. Research indicates that intestinal infection is reduced in infants who receive biologically acidified infant formula.…”
Section: Introductionmentioning
confidence: 99%
“…lactis (B. lactis), marketed as BB-12, is a commercially available probiotic strain that is considered one of the most well characterized and studied probiotics, particularly in reducing illness in young children. (Black et al, 1989;Alm et al, 1993;Link-Amster et al, 1994;Saavedra et al, 1994;Schiffrin et al, 1995;Obradovic et al, 1996;Kankaanpaa et al, 1998;Phuapradit et al, 1999;Matsumoto et al, 2001;Chouraqui et al, 2004;Amrouche et al, 2006a, b;Taipale et al, 2011). Long-term consumption of BB-12-fortified formula at levels as high as 240 billion colony-forming unit (CFU) per day has been shown to be safe and well tolerated (Abi-Hanna et al, 1998;Saavedra et al, 2004).…”
Section: Introductionmentioning
confidence: 99%